2021
DOI: 10.48550/arxiv.2102.08785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single particle tunneling spectroscopy and superconducting gaps in layered iron based superconductor KCa$_{2}$Fe$_{4}$As$_{4}$F$_{2}$

Wen Duan,
Kailun Chen,
Wenshan Hong
et al.

Abstract: We perform scanning tunneling microscopy/spectroscopy study on the layered iron based superconductor KCa2Fe4As4F2 with a critical temperature of about 33.5 K. Two types of terminated surfaces are generally observed after cleaving the samples in vacuum. On one commonly obtained surface, we observe a full gap feature with energy gap values close to 4.6 meV. This type of spectrum shows a clean and uniform full gap in space, which indicates the absence of gap nodes in this superconductor. Quasiparticle interferenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…[31] In KCa 2 Fe 4 As 4 F 2 , the √ 2 × √ 2 reconstruction of the 057404-4 potassium or calcium atoms is observed by STM on each cleaved surface. [32] The √ 2 × √ 2 surface reconstruction has also been observed in many other FeAs-based superconductors. [33−38] The common occurrence of the √ 2 × √ 2 surface reconstruction provides a general scenario to understand the (𝜋,𝜋) band folding commonly observed in the FeAs-based superconductors.…”
mentioning
confidence: 85%
“…[31] In KCa 2 Fe 4 As 4 F 2 , the √ 2 × √ 2 reconstruction of the 057404-4 potassium or calcium atoms is observed by STM on each cleaved surface. [32] The √ 2 × √ 2 surface reconstruction has also been observed in many other FeAs-based superconductors. [33−38] The common occurrence of the √ 2 × √ 2 surface reconstruction provides a general scenario to understand the (𝜋,𝜋) band folding commonly observed in the FeAs-based superconductors.…”
mentioning
confidence: 85%
“…The flat area is the √ 2× √ 2 reconstructed surface by half amount of K or Ca atoms of the related layer after the cleavage, while there are many hollows with different sizes on the surface which may be the assembled vacancies [28]. However, the tunneling spectra measured in this kind of area show very homogeneous feature with coherence peak energies at about 4.3 ± 0.2 meV, and Fig.…”
mentioning
confidence: 94%
“…Several Fermi surfaces with multiple and nodeless gaps were observed by the angle-resolved photoemission spectroscopy (ARPES) [27], and some of the bands are very shallow. It is found that the dominant contribution of density of states arises from the shallow α pocket based on STM/STS measurements [28]. Hence, the VBS should be interesting in this multiple and shallow band superconductor.…”
mentioning
confidence: 98%
See 1 more Smart Citation